Amelia Bedelia, bookworm - Parish, Herman; Sweat, Lynn (New York : Greenwillow Books, 2003)
The literal-minded housekeeper causes chaos at her local library when she stops by to help the librarian.
Ages 5 and up.
Keywords: Amelia-Bedelia (Fictitious character) -- Juvenile fiction; Libraries -- Fiction; Humorous stories; EZ